Evaluation the Effect of Seed Priming with Zinc Sulfate on Photosynthesis and Yield Components, of Two Varieties of Cowpea (Vigna unguiculata L.) under Water Deficit Stress - Sara Raisi Bidkani; Mohammad Javad Zarea (پژوهش‌های حبوبات ایران, 2024)
IntroductionCowpea is among the most important plants of the legume family, being a good source of protein, fiber, and essential nutrients. Cowpeas are also cost-effective and have high nutritional value. It has been shown that priming seeds with zinc can improve seedling vigor, growth, and overall plant performance. Priming seeds with ZnSO4 has been found to increase plant tolerance to environmental stress such as drought and water deficiency. Overall, it has been well-documented that priming seeds with zinc can be a promising practice for improving crop productivity under environmental stresses. Considering the simplicity of this technique and the widespread use of priming seeds with nutrients, this experiment was conducted to investigate the effect of priming seeds with zinc sulfate on some physiological traits, improvement in drought tolerance, and seed yield of two cowpea varieties. Materials and Methods The present study was conducted to investigate the effect of seed priming with zinc sulfate on the plant growth and yield performance of two different varieties of cowpea (Vigna unguiculata L.) under two different soil water content conditions. The experiment was carried out as a pot experiment in 2022 at the greenhouse of the Faculty of Agriculture, Ilam University. Treatments were replicated four times. The three main factors included the irrigation level (irrigation at 70% or 50% of the field capacity), the cowpea genotype (local and Mashhad), and the priming of seeds with zinc sulfate (hydropriming, prime level 1, prime level 2). Seeds were primed in either 0.14% or 0.28% zinc solution. ZnSO4.7H2O was used as the source of zinc. After surface sterilization, seeds were soaked in a solution with different concentrations of zinc sulfate (‎0.14% or 0.28%‎) for 5 hours at a ratio of 1:3 distilled seed to solution (w.v-1). 20 seeds were planted in each pot. Plants at the 4-5 leaf stage were subjected to well-watered and water-stressed conditions. At the 50% flowering stage, leaf samples were randomly taken from 5 plants in each pot, and various plant growth and physiological characteristics such as fresh and dry weight, plant height, leaf surface area and weight, as well as the rates of photosynthesis and transpiration, leaf relative humidity, and leakage rate were measured. Results and Discussion The results of the analysis of variance of the present study showed that the effect of water deficiency on some growth, physiological and biochemical traits such as leaf area and weight, photosynthesis rate, transpiration intensity, electrolyte leakage, water ratio per thousand seed weight, and harvest index was significant. Treatments affected by seed priming with zinc showed better growth performance under stress conditions than control treatments (no priming). Additionally, the effect of the variety on traits such as photosynthesis rate, and harvest index was significant. The highest leaf weight (7.10 g) was observed in the irrigation treatment with 70% of field capacity (FC), Mashhad variety, and prime level 2, while the lowest leaf weight (2.11 g) was recorded in the irrigation treatment with 50% of crop capacity, local variety, and hydropriming. The Mashhad cultivar exhibited a higher photosynthesis rate (4.99 μMol CO2.m-2.S-1) than the local cultivar (4.65 μMolCO2.m-2.S-1). The application of 70% FC led to a two-fold increase in the rate of photosynthesis (6.07 μMol CO2.m-2.S-1) compared to irrigation with 50% of FC (3.56 μMol CO2.m-2.S-1). The highest and lowest transpiration rates were observed under the conditions of no stress in the Mashhad cultivar (160.1 mmol H2O.m-2.S-1) and under the conditions of stress in the local cultivar (0.72 mmol H2O.m-2.S-1), respectively. Under low irrigation, the lowest (46%) and highest (49%) percentage of electrolyte leakage were obtained in priming level 2 and hydropriming, respectively. Regarding the traits related to yield, the highest number of pods per plant (8.22) was obtained in the Mashhad variety under well-irrigation conditions (70% FC), and the lowest amount (5.56) was obtained in the local variety with 50% FC. Under well-watered conditions (70% FC), the Mashhad variety had an 18% superiority in the number of seeds per plant compared to the local variety. The highest amount of seed yield in the pot was obtained under well-watered conditions and priming with 0.28% zinc solution resulting in a 28% increase compared to 50% FC and hydroprime. The use of the Mashhad cultivar under well-watered conditions led to the production of the highest harvest index (53.85%), while applying water deficit reduced the harvest index to 39.71%. ConclusionsDrought stress and water deficiency are the most significant constraints contributing to reduced bean yields in arid and semi-arid regions. The findings of the present study indicate that water deficit stress can significantly decline plant yield, but seed priming with zinc could mitigate the negative effects of water stress, particularly on the plant's physiological traits. Priming seeds with zinc resulted in improved photosynthesis and subsequently increased seed yield compared to control seeds